Atmospheric polychlorinated biphenyl (pcb) inputs to a coastal city near the marmara sea - Gunindi, Manolya; Tasdemir, Yucel (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Recent studies have shown that polychlorinated biphenyl (PCB) levels are high in coastal sites. Various types of deposition events, including dry deposition, air-water exchange and wet deposition, were analyzed as part of the study to illustrate the pollution level. The atmospheric levels and deposition mechanisms of 82 PCBs were investigated in Mudanya, a coastal city in Turkey. A total of 175 samples and 112 blanks were collected. Air-water exchange and particle phase dry deposition fluxes were 120 +/- 90 ng/m(2)-d and 125 +/- 160 ng/m(2)-d, respectively. The wet-dry deposition sampler (WDDS) consisted of two reservoirs, wet and dry. Collected with the WDDS, the dry deposition flux was 21 +/- 20 ng/m(2)-d, and the wet deposition fluxes (during the rainy period) were 145 +/- 130 ng/m(2)-d and 195 +/- 270 ng/m(2)-d for the dissolved and particulate phases, respectively. Mass transfer coefficients (MTCs), dry deposition velocities and washout ratios were calculated and compared with the literature values. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Deposition; Rain; Deposition velocity; MTC; Washout ratio; POLYCYCLIC AROMATIC-HYDROCARBONS; WATER-SURFACE SAMPLER; DRY DEPOSITION FLUXES; WET DEPOSITION; URBAN SITE; ORGANOCHLORINE COMPOUNDS; PHASE DEPOSITION; INDUSTRIAL SITE; AIR; LAKE; Environmental Sciences & Ecology; Marine & Freshwater Biology